HISTORICAL AND CONTEMPORARY UTILIZATION OF DICTIONARIES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a comprehensive overview of the primary challenges in English lexicography, highlighting the complexities lexicographers face in defining and documenting an ever-evolving language. The article concludes by emphasizing the importance of maintaining inclusivity and accuracy, positioning lexicography as both a linguistic and cultural endeavor essential for reflecting the language accurately. This summary provides insight into the intricate work that underpins English lexicography and highlights its ongoing importance in adapting to linguistic and social changes.